2009
DOI: 10.1002/aic.12082
|View full text |Cite
|
Sign up to set email alerts
|

Solid–liquid equilibrium of substrates and products of the enzymatic synthesis of ampicillin

Abstract: The solid-liquid equilibrium of precursors and products of the enzymatic synthesis of ampicillin (AMP) [6-aminopencillanic acid (6-APA) and D(À)phenylglycine (PG)] was investigated at different temperatures (283-298 K) and pHs (5.5-7.5). Solubility data were obtained using an analytical methodology. Equilibrium dissociation constants were experimentally measured at several temperatures for AMP, 6-APA, PG, and D(À)phenylglycine methyl ester. A model based on the simplified perturbed hard sphere theory proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…They modeled amino acids as Lennard-Jones spheres with dipole-dipole interactions. Santana et al [22] showed that this model fails to quantitatively predict the solubility of ampicillin, d-phenylglycine and 6-aminopenicillanic acid as a function of pH even adjusting five parameters. Pradhan and Vera [6], using an equation similar to that proposed by Gupta and Heidemann [9] with the NRTL equation, correlated the dlalanine solubility as a function of pH, with good agreement with the experimental data in the vicinity of the isoelectric point.…”
Section: List Of Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…They modeled amino acids as Lennard-Jones spheres with dipole-dipole interactions. Santana et al [22] showed that this model fails to quantitatively predict the solubility of ampicillin, d-phenylglycine and 6-aminopenicillanic acid as a function of pH even adjusting five parameters. Pradhan and Vera [6], using an equation similar to that proposed by Gupta and Heidemann [9] with the NRTL equation, correlated the dlalanine solubility as a function of pH, with good agreement with the experimental data in the vicinity of the isoelectric point.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…Fig. 9 shows the chemical structures of two ␤-lactam compounds: the antibiotic ampicillin and its precursor 6-aminopenicillanic acid, for which solubility data as a function of pH and temperature are available [22]. In this case, one can apply Eq.…”
Section: Solubility Of ˇ-Lactam Compounds As a Function Of Ph And Temmentioning
confidence: 99%
“…In the enzymatic synthesis of amoxicillin from hydroxyphenylglycine methyl ester (HPGM) and 6-APA, as indicated in Figure 1, the Penicillin G Acylase (PGA) catalyzes both the synthesis of the antibiotic by coupling (Reaction 1) and the undesired hydrolysis of the substrate (Reaction 2) and its product (Reaction 3), generating hydroxyphenylglycine (HPG) and alcohol. Therefore, the yield of the process depends on the kinetic rates of these three reactions, where the antibiotic acts as the intermediate component within a set of series-parallel reactions (Santana et al, 2010). Thus, the concentration curve of antibiotic reaches a maximum value, beyond which the hydrolytic reactions prevail.…”
Section: Introductionmentioning
confidence: 99%
“…Literature measurements concerning the solidliquid equilibrium of β-lactam antibiotics are scarce (Santana et al, 2010). Diender et al (1998) determined the solubility of HPG, 6-APA and AMOX in water as function of pH at 298.15 K according to the analytical method proposed by Gude et al (1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation